The management of dysplastic naevi: a survey of Australian dermatologists. (2nd November 2017) - Wall, Nerilee; De'Ambrosis, Brian; Muir, Jim
Abstract: Background/Objectives: The management of dysplastic naevi based on histopathological grading is a contentious issue. Comprehensive management guidelines are lacking and the approach taken varies between clinicians. The authors sought to understand how Australian dermatologists approach the management of biopsy‐proven dysplastic naevi, and the impact of grading of dysplasia upon this management. Methods: In total, 547 Fellows of the Australasian College of Dermatologists were surveyed and 218 responses were collected (40% response rate). Results: Although all dermatologists surveyed would re‐excise an incompletely removed severely dysplastic naevus, opinion was divided over whether to treat such a lesion as an in situ melanoma or a dysplastic naevus, with 55% of respondents using a 5‐mm margin and the remainder opting for narrow margin re‐excision. When the same lesion was reported to be clear of margins by 1 mm after biopsy and the clinical suspicion for melanoma was high, 44% would re‐excise with a 5‐mm margin. Conclusions: The approach of Australian dermatologists to the management of dysplastic naevi varies between clinicians, reflecting the problems raised by the validity of histopathological grading.